Políticas restritivas aos japoneses no Estado do Paraná, 1930-1950 (de cores proibidas ao perigo amarelo) - Kimura, Rosangela (2006)
As away to control the foreigns dictatorial regime (Estado Novo) restricted the press, closed schools, created a registration system capable as controlling and survillance of the immigrant. Paraná was the precursor of almost all repressive action the immigrants (German, ltalian and Japanese), during the Second World War, it also evacuated areas considered "national security", through order from the DOPS (department of social and politic order), executed by the local responsible department, in September 25th in 1942. It intende to, after the expulsion of a small groups of Japanese from Paraná's sea shore, showing the moment that authority thought they represented danger to Brazilian nation. It is noted to check, still the situation of Japanese community divided in two factions, those who believed in Japanese victory, leadered by Shindô Renmei society, and who accept its defeat.